Formation And Evaluation Of Silicon Substrate With Highly-Doped Porous Si Layers Formed By Metal-Assisted Chemical Etching - Ono, Takahito; Li, Yi Jie; Wang, Zhuqing; Toan, Nguyen Van; Samat, Khairul Fadzli (Springer, 2021)
Porous silicon (Si) is a low thermal conductivity material, which has high potential for thermoelectric devices. However, low output performance of porous Si hinders the development of thermoelectric performance due to low electrical conductivity. The large contact resistance from nonlinear contact between porous Si and metal is one reason for the reduction of electrical conductivity. In this paper, p- and n-type porous Si were formed on Si substrate by metal-assisted chemical etching. To decrease contact resistance, p- and n-type spin on dopants are employed to dope an impurity element into p- and n-type porous Si surface, respectively. Compared to the Si substrate with undoped porous samples, ohmic contact can be obtained, and the electrical conductivity of doped p- and n-type porous Si can be improved to 1160 and 1390 S/m, respectively. Compared with the Si substrate, the special contact resistances for the doped p- and n-type porous Si layer decreases to 1.35 and 1.16 mΩ/cm2, respectively, by increasing the carrier concentration. However, the increase of the carrier concentration induces the decline of the Seebeck coefcient for p- and n-type Si substrates with doped porous Si samples to 491 and 480 μV/K, respectively. Power factor is related to the Seebeck coefcient and electrical conductivity of thermoelectric material, which is one vital factor that evaluates its output performance. Therefore, even though the Seebeck coefcient values of Si substrates with doped porous Si samples decrease, the doped porous Si layer can improve the power factor compared to undoped samples due to the enhancement of electrical conductivity, which facilitates its development for thermoelectric application.